WORKSHOP PEMBUATAN PROPOSAL PTK DAN PRODUKTIVITAS USAHA KULINER DALAM RANGKA PENGEMBANGAN KESEJAHTERAAN DI JAKARTA TIMUR - Etin Solihatin; Moch Sukardjo; Roby Ibnu Syarifain; Jhony Lagun Siang (Bahasa Indonesia, 2020)
Abstract This research was designed to develop the ability to make the Classroom Action Research Proposal and culinary business in tekwan production. The teacher could not fulfil the promotion requirement because of the lack of ability to create an classroom action research proposal. The other problem is how to develop a culinary business by making Tekwan as a new product to increase citizen prosperity. The solution to solve this first problem that used in this research were conducting Classroom Action Research Proposal Workshop, then continued with assistance in the creating process and providing resource reference to get funding by Ministry of Education and Culture through the internet. The solution that used for the second problem in this research was by practising in tekwan production, continued by teaching how to make an eye-catching package and accessing market to make a sustainable profit and achieving prosperity. This activity was carried during COVID-19 Pandemic through online media such as Zoom and Youtube by uploading video about Tekwan production https://m.youtube.com/watch?v=9mlis3z7fCc. While the Classroom Action Research Proposal the workshop was upload by using the following link https://youtu.be/q_JRwwZyRzs with offline material such as Intellectual property right of Classroom Action Research Book EC00202017002. Abstrak Penulisan artikel ini bertujuan meningkatkan kemampuan membuat proposal Penelitian Tindakan Kelas (PTK) dan produktivitas usaha kuliner dalam pembuatan tekwan. Permasalahan pertama yang dihadapi dan sangat mendesak tentang kurangnya kemampuan membuat proposal Penelitian Tindakan Kelas bagi guru, sehingga syarat melaksanakan penelitian untuk kenaikan pangkat ada kendala. Permasalahan kedua bagaimana meningkatkan produktivitas usaha kuliner dalam rangkap pengembangan kesejahteraan. Solusi yang ditawarkan untuk masalah pertama yaitu melaksanakan workshop “Penelitian Tindakan Kelas”, dilanjutkan dengan pembuatan proposal dan pendampingan/konsultasi, serta mencari sumber dana baik via internet maupun dengan Kemendikbud. Solusi untuk masalah kedua praktek kuliner, dilanjutkan bagaimana usaha memasarkannya, mengemas yang menarik. Produktivitas usaha kuliner lancar maka kesejahteraan akan mengiringi. Setelah dilakukan pengabdian kepada masyarakat untuk produktivitas usaha kuliner dalam rangka pengembangan kesejahteraan, karena pandemi corona maka dilakukan secara online via Youtube: https://m.youtube.com/ watch?v=9mlis3z7fCc. Sedangkan pelatihan pembuatan proposal PTK dilakukan secara daring melalui zoom dan youtube dengan link sebagai berikut https://youtu.be/q_JRwwZyRzs dengan HKI buku PTK EC00202017002.